2022
DOI: 10.1108/jfbm-10-2021-0130
|View full text |Cite
|
Sign up to set email alerts
|

We are in survival mode: how family-owned small foodservice firms in India responded to the Covid-19 pandemic

Abstract: PurposeThe purpose of this paper is to examine the crisis faced, strategies adopted, barriers for recovery and the future outlook by the operators of family-owned small foodservice business firms in responses to COVID-19. The COVID-19 pandemic has unfolded unprecedented challenges, severely disrupted the family-run small foodservice business units and often put them on the brink of closure of business.Design/methodology/approachThe methodology adopted is a qualitative research approach. The data for the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…It was argued that external stakeholders with embeddedness in the family show transparency and also commitment. Piramanayagam et al (2022) investigated how family-owned small food service firms survived the pandemic in India and found that most of the family-owned businesses did not have a crisis prevention plan and only adopted reactive strategies. Nwuke et al (2020) emphasise that the survival of family businesses is influenced by internal factors associated with the founders.…”
Section: Survival Strategies For Family Business Smesmentioning
confidence: 99%
“…It was argued that external stakeholders with embeddedness in the family show transparency and also commitment. Piramanayagam et al (2022) investigated how family-owned small food service firms survived the pandemic in India and found that most of the family-owned businesses did not have a crisis prevention plan and only adopted reactive strategies. Nwuke et al (2020) emphasise that the survival of family businesses is influenced by internal factors associated with the founders.…”
Section: Survival Strategies For Family Business Smesmentioning
confidence: 99%
“…The research has estimated that between 70–95% of the businesses in the world are operated by families and that these businesses employ about 50% of the world’s workforce (Obermayer et al. , 2021; Piramanayagam et al. , 2022; Royer and Bradley, 2020; Veloso et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this COVID-19 crisis had a major impact on small family businesses that operated in the accommodation industry. This is quite challenging, since small businesses are very vulnerable to crisis (Herbane, 2010, 2013; Piramanayagam et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations